Multiple sclerosis – new strategies of therapy - Palasik, Witold (Przewodnik Lekarza/Guide for GPs, 2007)
Multiple sclerosis (MS) is a common neurological disorder and a major cause of disability among young adults. Despite great and fast progress of research and expectation following interferon beta and glatiramer acetate development there is still no evidence of a significant breakthrough in MS treatment. For these reasons research continues to create new and more efficient drugs which could modify, with permanent effect, the natural progress of MS.